So what'cha want? The impact of individualised rewards on associative learning in psychopathic offenders. (April 2022) - Glimmerveen, Johanna C.; Maes, Joseph H.R.; Bulten, Erik; Scheper, Inge; Brazil, Inti A.
Abstract: Psychopathic individuals typically present with associative learning impairments under explicit learning conditions. The present study aimed to investigate whether the formation of stimulus-outcome associations, as well as updating of these associations after changed contingencies, could be improved by using rewards with sufficiently high subjective values. To this end, 20 psychopathic offenders, 17 non-psychopathic offenders and 18 healthy controls performed a passive avoidance task with a reversal phase under three motivational conditions, using naturalistic rewards. The subjective values of the rewards were assessed a priori for each individual participant using a visual analogue scale. The correspondence of these values to their internal representation was confirmed by analyses of brain potentials. Analyses using both signal detection theory and classical approaches indicated that psychopathic offenders performed worse compared to the other groups during passive avoidance learning. However, using the signal detection approach, we found this deficiency to be present only when a hypothetical reward was used ('neutral reward' condition), whereas psychopathic offenders performed similar to the other groups when naturalistic rewards could be obtained ('low reward' and 'high reward' conditions). Furthermore, traditional analyses suggested that psychopathic offenders had more hits than the other groups during reversal learning, but the signal detection approach indicated that no effects of group or condition were present. Analysis of win-stay and lose-shift behaviour showed that psychopathic offenders were less likely to stay with a rewarded response during passive avoidance learning in the neutral reward condition. In addition, regardless of experimental phase or condition, psychopathic offenders were less likely to stop responding to a particular stimulus after receiving negative feedback. Although the approaches employed did not lead to unequivocal results, our findings suggest that psychopathic offenders do have the ability to adapt their behaviour to environmental contingencies when positive reinforcers with sufficiently high subjective values are used.